Legal Examination of Military Court Decisions on the Criminal Actions of Indonesian Navy Members in Selling Illegal Timber - Dandy Ramadhan; Rahayu Subekti (Jurnal Jurisprudence, 2025)
ABSTRACT Research Objective: This research aims to juridically analyze the Decision of the High Military Court III of Surabaya No. 114-K/PMT.III/BDG/AL/VII/2023 on the involvement of two active members of the Indonesian National Army’s Navy in the crime of transporting timber forest produce without valid documents (illegal logging). This analysis focuses on the application of the general norms of the criminal law, the forestry law, and the military law that intersect in this case, as well as how far the “equality before the law” principle is applied to military personnel. Research Method: This research employed the normative juridical method (doctrinal method) with an analytical approach on legal regulations, legal doctrines, as well as court decisions. The analyzed legal materials include Law No. 34 of 2004 on the Indonesian National Army, Law No. 18 of 2013 on the Prevention and Elimination of Forest Destruction, the Criminal Code, the Military Criminal Code, Law No. 31 of 1997 on the Military Court, as well as the Governmental Regulation No. 5 of 2021. Result: Results of this research show that the action of the Indonesian Navy’s personnel in this case was proven to violate positive law violations both in the realm of general crime and the ream of military criminal law. Judges’ decision was deemed accurate as it considered legal evidence, the losses of the state, as well as the legal equality principle without discriminating against the military institution status. The imposition of penalization in the form of imprisonment and fines in this case also reflected consistency in the application of the legal state principle in military justice. Research Application: This research may become a reference to enforce the law against state apparatus, especially military personnel, who committed legal violations outside of their authority. Apart from that, this analysis may be used as a material for evaluation and improvement of the internal monitoring system in the Indonesian National Army’s environment so that it may be more transparent and accountable. Novelty: The “equality before the law” theory profoundly analyzes this military decision using the ratio decidendi theory. This research offers an interdisciplinary analysis between military law, environmental law, the law on permits, and the principle of constitutional justice in one decision, as well as the confirmation that the “equality before the law” principle must still be enforced for all citizens, including the state defense apparatus. Keywords: Military Decision, Justice, Crime, Illegal Logging.   ABSTRAK Tujuan Penelitian: Penelitian ini bertujuan untuk menganalisis secara yuridis Putusan Pengadilan Militer Tinggi III Surabaya No. 114-K/PMT.III/BDG/AL/VII/2023 tentang keterlibatan dua anggota aktif TNI Angkatan Laut dalam tindak pidana pengangkutan hasil hutan kayu tanpa dokumen yang sah (illegal logging). Analisis ini berfokus pada penerapan norma-norma umum hukum pidana, hukum kehutanan, dan hukum militer yang bersinggungan dalam perkara ini, serta sejauh mana asas “kesetaraan di hadapan hukum” diterapkan kepada personel militer. Metode Penelitian: Penelitian ini menggunakan metode yuridis normatif (metode doktrinal) dengan pendekatan analitis terhadap peraturan perundang-undangan, doktrin hukum, serta putusan pengadilan. Bahan hukum yang dianalisis meliputi Undang-Undang Nomor 34 Tahun 2004 tentang Tentara Nasional Indonesia, Undang-Undang Nomor 18 Tahun 2013 tentang Pencegahan dan Pemberantasan Perusakan Hutan, Kitab Undang-Undang Hukum Pidana, Kitab Undang-Undang Hukum Pidana Militer, Undang-Undang Nomor 31 Tahun 1997 tentang Peradilan Militer, serta Peraturan Pemerintah Nomor 5 Tahun 2021. Hasil: Hasil penelitian ini menunjukkan bahwa tindakan personel TNI AL dalam perkara ini terbukti melanggar hukum positif baik dalam ranah pidana umum maupun ranah hukum pidana militer. Putusan hakim dinilai tepat karena mempertimbangkan alat bukti yang sah, kerugian negara, serta asas persamaan hukum tanpa membeda-bedakan status kelembagaan militer. Penjatuhan pidana berupa pidana penjara dan denda dalam perkara ini juga mencerminkan konsistensi penerapan asas negara hukum dalam peradilan militer. Aplikasi Penelitian: Penelitian ini dapat menjadi acuan untuk menegakkan hukum terhadap aparatur negara, khususnya personel militer, yang melakukan pelanggaran hukum di luar kewenangannya. Selain itu, analisis ini dapat digunakan sebagai bahan evaluasi dan penyempurnaan sistem pengawasan internal di lingkungan Tentara Nasional Indonesia agar lebih transparan dan akuntabel. Kebaruan: Teori "kesetaraan di hadapan hukum" menganalisis keputusan militer ini secara mendalam menggunakan teori ratio decidendi. Penelitian ini menawarkan analisis interdisipliner antara hukum militer, hukum lingkungan, undang-undang perizinan, dan asas keadilan konstitusional dalam satu putusan, sekaligus penegasan bahwa asas "kesetaraan di hadapan hukum" tetap harus ditegakkan bagi seluruh warga negara, termasuk aparat pertahanan negara. Kata Kunci: Keputusan Militer, Keadilan, Kejahatan, Pembalakan Liar